The role of periodontal treatment on the reduction of hemoglobinA1c, comparing with existing medication therapy: a systematic review and meta-analysis - Umezaki, Yojiro; Yamashita, Akiko; Nishimura, Fusanori; Naito, Toru (Frontiers in Clinical Diabetes and Healthcare, 2025)
BackgroundDiabetes mellitus (DM) is linked to complications such as retinopathy, nephropathy, neuropathy, and cardiovascular disease, impacting patient quality of life and increasing healthcare costs. Periodontal disease, more prevalent in diabetic patients, is associated with worsened glycemic control and systemic inflammation, suggesting a possible bidirectional relationship. While some studies indicate periodontal treatment may improve glycemic control and reduce inflammation, overall evidence is inconsistent. It remains unclear if periodontal therapy reliably enhances diabetes outcomes or if certain patient subgroups benefit more than others.ObjectiveTo systematically review randomized controlled trials (RCTs) evaluating the effects of periodontal therapy on glycemic control (HbA1c) and systemic inflammation (CRP) in type 1 and type 2 diabetes patients.MethodsFollowing PRISMA guidelines, a comprehensive PubMed search identified RCTs comparing HbA1c and CRP outcomes in diabetic patients with periodontal therapy versus controls. Inclusion criteria required at least three to six months of follow-up. Meta-analyses using a random effects model were conducted for HbA1c and CRP changes.ResultsEleven studies met inclusion criteria. Meta-analyses showed significant reductions in HbA1c at three months (-0.64; CI95%=-0.96 to -0.32; I2 = 73%) and six months (-0.33; CI95%=-0.65 to -0.01; I2 = 12%). CRP also declined significantly, indicating an improvement in systemic inflammation.ConclusionPeriodontal therapy appears to significantly reduce HbA1c and CRP levels over short-term periods in diabetic patients, suggesting potential as a beneficial adjunct to diabetes management. These findings support incorporating periodontal care into diabetes treatment to reduce systemic inflammation and potentially lower healthcare costs. Future long-term, standardized RCTs are needed to confirm sustained effects and investigate responses in diverse patient populations.